PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN KEMAMPUAN EKSPLORASI MATEMATIS PESERTA DIDIK SMP - nuraeni azizah; dinny mardiana; samnur saputra (Universitas Islam Nusantara, 2018)
This reseach was aimed to explore the low students’ ability of math. One of the way for learning could be applied to improve the students ability in exploring of math is Think Pair Share (TPS) model. The purpose of this reseach to know: the improvement of the students’ ability in exploring of math used “Think Pair Share(TPS)” and responded the students to learning of math about this learning, the metode was used is cuasi eksperimen metode with reseach design in pretest-posttest control group design.This reseach was conducted at one of SMP Swasta in Bandung. The population were all students eight grade. Students eight grade B class group as control class. Eksperiment class was given “Think Pair Share(TPS)” learning model and control class convensional learning model instrument was used to test ability about the explore math, the students respons qualitatif data and quantitatif data. Based on the result of analysis in tets math exploring ability was concluded, the improvement of the students’ability in exploring of math with” Think Pair Share (TPS)”was more students used convensional model learning, students answered the positif respons to “Think Pair Share (TPS)” learning model.